2013
DOI: 10.1158/0008-5472.can-12-3023
|View full text |Cite
|
Sign up to set email alerts
|

SRC Signaling Is Crucial in the Growth of Synovial Sarcoma Cells

Abstract: Synovial sarcoma is a soft-tissue malignancy characterized by a reciprocal t(X;18) translocation encoding a chimeric transcriptional modifier. Several receptor tyrosine kinases have been found activated in synovial sarcoma; however, no convincing therapeutic concept has emerged from these findings. On the basis of the results of phosphokinase screening arrays, we here investigate the functional and therapeutic relevance of the SRC kinase in synovial sarcoma. Immunohistochemistry of phosphorylated SRC and its r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 39 publications
(56 reference statements)
2
50
0
2
Order By: Relevance
“…Primary cathepsin B antibody was obtained from D. J. Buttle, University of Sheffield, UK (Buttle et al, 1988). Antibodies against the following proteins were purchased from manufacturers as listed below: actin (Sigma-Aldrich, St. Louis, MO) (Zhou et al, 2005), calnexin (Millipore, Carrigtwohill, Ireland) (Methner and Mayfield, 2010), EGF receptor (Cell Signaling Technologies, Danvers, MA) (Kawahara et al, 2010), Grb-2 (Cell Signaling Technologies) (Benitez et al, 2011), IGF-1R (Cell Signaling) (Michels et al, 2013), IRS-2 (Cell Signaling) (Gao et al, 2014), Lamp-1 (Cell Signaling), LC-3B (Cell Signaling) (Tong et al, 2012), MAPK (Cell Signaling) (Michels et al, 2013), Akt (Cell Signaling), p-IGF-1Rb (Cell Signaling), p-MAPK (Cell Signaling), p-Akt (Cell Signaling) (Michels et al, 2013), p-Shc A (Cell Signaling) (Krall et al, 2011), RAS (Cell Signaling), Shc A (Cell Signaling), N-Shc (BD Biosciences, San Jose, CA) (Tarr et al, 2002). The secondary goat fluor-568 anti-rabbit antibody was from Invitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…Primary cathepsin B antibody was obtained from D. J. Buttle, University of Sheffield, UK (Buttle et al, 1988). Antibodies against the following proteins were purchased from manufacturers as listed below: actin (Sigma-Aldrich, St. Louis, MO) (Zhou et al, 2005), calnexin (Millipore, Carrigtwohill, Ireland) (Methner and Mayfield, 2010), EGF receptor (Cell Signaling Technologies, Danvers, MA) (Kawahara et al, 2010), Grb-2 (Cell Signaling Technologies) (Benitez et al, 2011), IGF-1R (Cell Signaling) (Michels et al, 2013), IRS-2 (Cell Signaling) (Gao et al, 2014), Lamp-1 (Cell Signaling), LC-3B (Cell Signaling) (Tong et al, 2012), MAPK (Cell Signaling) (Michels et al, 2013), Akt (Cell Signaling), p-IGF-1Rb (Cell Signaling), p-MAPK (Cell Signaling), p-Akt (Cell Signaling) (Michels et al, 2013), p-Shc A (Cell Signaling) (Krall et al, 2011), RAS (Cell Signaling), Shc A (Cell Signaling), N-Shc (BD Biosciences, San Jose, CA) (Tarr et al, 2002). The secondary goat fluor-568 anti-rabbit antibody was from Invitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…5F). Since DCA treatment did not decrease Src phosphorylation at Tyr 416 below baseline, we sought to better understand the interaction between DCA and Src by investigating phosphorylation at Tyr 527 , the inhibitory Src phosphorylation site (49). We found that DCA treatment stimulated Src Tyr 527 phosphorylation, which was maximized at 2 h (Fig.…”
Section: Dca-induced Inhibition Of Cell Proliferation Is Mediated By mentioning
confidence: 95%
“…With the use of immunohistochemistry and Western blotting, the total Src and phosphorylated Src (Y419) were found to be activated in human sarcoma tissues (leiomyosarcoma, high-grade osteosarcoma and liposarcoma) and sarcoma cell lines (osteosarcoma, Ewing's sarcoma, leiomyosarcoma and rhabdomyosarcoma) (45). Furthermore, Src was identified as one of the most strongly phosphorylated kinases in synovial sarcoma cells (46). Src activity was demonstrated to be upregulated in anoikis-resistant human osteosarcoma cells, SAOS-2, compared with their parental population (47).…”
Section: Function Of Src In Sarcomamentioning
confidence: 99%